Ultrafast dynamical charge-lattice coupling in rare-earth nickelate thin films studied by time-resolved terahertz spectroscopy - Kinha, Monu (2023)
Rare-earth nickelates exhibit a rich phase diagram formed by the complex interplay of intertwined and competing energetics of fundamental entities. To unwind the coupling and interaction mechanisms of fundamental entities underneath, time-resolved terahertz (THz) spectroscopy was implemented to understand non-equilibrium carrier and lattice dynamics of epitaxial thin films of La x Eu1-x NiO3 (x = 0, 0.25, 0.50, 1) systems, where x = 0 is insulating while remaining are metallic at room temperature. The THz transmittance of the insulating and metallic phases exhibit contrasting photo-induced phases associated with bi-exponential and mono-exponential relaxation mechanisms, respectively. A pronounced oscillatory feature superimposed on the mono-exponential relaxation manifests only in the metallic phase. As ascribed to the acoustic phonons, the 'x' dependent behavior of this feature reveals an inverse relation between the strength of electron-phonon coupling and the magnitude of conductivity. In the insulating state, in contrast, the relaxation time constants are associated with the recovery of charge-ordering and electron-phonon thermalization. This dynamical lattice-charge interaction study demonstrates use of this ultrafast phenomena in nickelate thin films in new generation ultrafast photo-acoustic devices as an alternate to conventional surface acoustic wave device.